Lifestyle management of polycystic ovary syndrome: a single-center study in Bosnia and Herzegovina - Jasmina Djedjibegovic; Aleksandra Marjanovic; Ilhana Kobilica; Amila Turalic; Aida Lugusic; Miroslav Sober (AIMS Press, 2020)
Background: Polycystic ovary syndrome (PCOS) is a complex endocrinopathy affecting up to 20% of pre-menopausal women. The most recent international guidelines set lifestyle management as the cornerstone of the PCOS treatment. Still, there is a paucity of data on the implementation of lifestyle management in clinical practice. This cross-sectional study aimed to explore physicians-reported practices in PCOS lifestyle management in the Sarajevo Canton, Bosnia and Herzegovina (BiH). The profession of dietetics is not legally recognized in BiH. Nutritional interventions in health promotion and disease treatment are provided by medical professionals. Methods: Data were collected by a paper-based questionnaire distributed during March-May 2018 in the Public Institution Health Centre of Sarajevo Canton. Results: Forty-six physicians (response rate of 80.7%) completed the questionnaire. An initial treatment plan based solely on lifestyle measures (diet + physical activity), as recommended by current guidelines was reported by 34.8% of physicians. Although dietary interventions were rated as highly relevant in PCOS management by the vast majority of physicians, only one-half reported recording patients' adherence and 45.7% of physicians were unsure of the effectiveness of the lifestyle interventions in their patients. Conclusion: PCOS lifestyle management in the study setting is sub-optimal. Additional education on effective PCOS lifestyle management strategies would be beneficial, especially for physicians with less than 15 years in practice. Possible obstacles to better physicians' engagement in PCOS lifestyle management should be further investigated.